Phylogenetic Analysis Indicates That Evasin-Like Proteins of Ixodid Ticks Fall Into Three Distinct Classes - Bhattacharya, Shoumo; Nuttall, Patricia Anne (Frontiers in Cellular and Infection Microbiology, 2021)
Chemokines are structurally related proteins that activate leucocyte migration in response to injury or infection. Tick saliva contains chemokine-binding proteins or evasins which likely neutralize host chemokine function and inflammation. Biochemical characterisation of 50 evasins from Ixodes, Amblyomma and Rhipicephalus shows that they fall into two functional classes, A and B, with exclusive binding to either CC- or CXC- chemokines, respectively. Class A evasins, EVA1 and EVA4 have a four-disulfide-bonded core, whereas the class B evasin EVA3 has a three-disulfide-bonded “knottin” structure. All 29 class B evasins have six cysteine residues conserved with EVA3, arrangement of which defines a Cys6-motif. Nineteen of 21 class A evasins have eight cysteine residues conserved with EVA1/EVA4, the arrangement of which defines a Cys8-motif. Two class A evasins from Ixodes (IRI01, IHO01) have less than eight cysteines. Many evasin-like proteins have been identified in tick salivary transcriptomes, but their phylogenetic relationship with respect to biochemically characterized evasins is not clear. Here, using BLAST searches of tick transcriptomes with biochemically characterized evasins, we identify 292 class A and 157 class B evasins and evasin-like proteins from Prostriate (Ixodes), and Metastriate (Amblyomma, Dermacentor, Hyalomma, Rhipicephalus) ticks. Phylogenetic analysis shows that class A evasins/evasin-like proteins segregate into two classes, A1 and A2. Class A1 members are exclusive to Metastriate ticks and typically have a Cys8-motif and include EVA1 and EVA4. Class A2 members are exclusive to Prostriate ticks, lack the Cys8-motif, and include IHO01 and IRI01. Class B evasins/evasin-like proteins are present in both Prostriate and Metastriate lineages, typically have a Cys6-motif, and include EVA3. Most evasins/evasin-like proteins in Metastriate ticks belong to class A1, whereas in Prostriate species they are predominantly class B. In keeping with this, the majority of biochemically characterized Metastriate evasins bind CC-chemokines, whereas the majority of Prostriate evasins bind CXC-chemokines. While the origin of the structurally dissimilar classes A1 and A2 is yet unresolved, these results suggest that class B evasin-like proteins arose before the divergence of Prostriate and Metastriate lineages and likely functioned to neutralize CXC-chemokines and support blood feeding.